Percepción de los estudiantes de Odontología acerca de la modalidad virtual con conexión remota en el aprendizaje y formación profesional (2021)
During the period 2020-2021, the perception of 5 students who were attending different semesters of the dentistry program was analyzed, through a semi-structured interview which contained questions oriented to the different opinions about remote and face to face classes, later each conversation was analyzed in the Atlas.ti software where conceptual axes were produced by means of codes that were compared with the theoretical framework.